Effect of hematopoietic growth factors on human blood monocytes/macrophages in in vitro culture. - Hassan, N F (1994)
The production of mature monocytes/macrophages is regulated by a group of hematopoietic growth factors, or colony-stimulating factors (CSF). We investigated the in vitro effect of human hematopoietic growth factors on human blood monocyte/macrophage differentiation and proliferation in short- and long-term in vitro cultures. The addition of macrophage CSF, granulocyte-macrophage CSF, and granulocyte CSF and interleukin-6 and interleukin-3 growth factors to monocyte/macrophage cultures induced morphological changes in cultured cells, including enhancement of cell growth and the formation of multinucleated giant cells, spindle-like cells, and fibroblast-like cells. In addition, CD4 and HLA-DR antigen expression was down regulated by the addition of growth factors without a change in the expression of other surface antigens, including CD3, CD11B, CD14, CD15, NK H1, and B1. The proliferating cell nuclear antigen was not detected in growth factor-treated nonadherent monocytes/macrophages in long-term cultures. Bromodeoxyuridine was incorporated in the adherent monocytes/macrophages, and intense staining in the small rounded cells which occur above the adherent cells in these cultures was observed after a 72-h pulse, indicating that monocytes/macrophages are slowly dividing cells.